Curcumin improves sclerosing cholangitis in Mdr2(−/−) mice by inhibition of cholangiocyte inflammatory response and portal myofibroblast proliferation - Baghdasaryan, Anna (2010)
BACKGROUND AND AIM: Chronic cholangiopathies have limited therapeutic options and represent an important indication for liver transplantation. Curcumin, the yellow pigment of the spice turmeric, has pleiotropic actions and attenuates hepatic damage in animal models of chemically-induced liver injury. Whether curcumin has beneficial effects in cholangiopathies is unknown. METHODS: Potential anti-cholestatic, anti-inflammatory and anti-fibrotic mechanisms of curcumin were explored in vivo in Mdr2(−/−) mice as a murine model of chronic cholangiopathy; as well as in vitro in a cholangiocyte cell line (HuCCT1) and portal myofibroblasts (MFBs) isolated from Mdr2(−/−) mice. RESULTS: Liver damage, cholestasis and fibrosis were reduced in Mdr2(−/−) mice after curcumin feeding. Moreover, curcumin inhibited cholangiocyte proliferation and expression of activation marker Vascular Cell Adhesion Molecule-1 (VCAM-1) in Mdr2(−/−) mice. Curcumin - similar to PPARγ synthetic agonist troglitazone - directly inhibited TNF-α induced inflammatory activation of cholangiocytes in vitro, whereas these beneficial effects of curcumin were largely blocked by a PPARγ synthetic antagonist. In addition, curcumin blocked proliferation and activation of portal MFBs by inhibiting ERK1/2 phosphorylation, thus contributing to reduced fibrogenesis. CONCLUSIONS: These results show that curcumin may have multiple targets in liver including activation of PPARγ in cholangiocytes and inhibition of ERK1/2 signalling in MFBs, thereby modulating several central cellular events in a mouse model of cholangiopathy. Targeting these pathways may be a promising therapeutic approach to cholangiopathies.